Study on the importance and impact of training in digital tools for MSMEs in Xicotepec (GEON Journal (Management, Organizations and Business), 2023)
Digital technologies are key to the economic development of companies, the "COVID-19" accelerated the adoption of digital tools to displace products and services. MSMEs in Mexico face challenges in the use and application of digital tools, lack the skills and knowledge to use them efficiently, there is a significant percentage without implementing them. We will evaluate the opinion of entrepreneurs on: "training in digital tools and its impact on the optimization of administrative management, thus finding challenges to face in improving the MSMEs of Xicotepec.Objectives. "Evaluate the opinion of MSMEs on the importance of training in digital tools and analyze its impact on the optimization of post-pandemic administrative management"Specific objectives "Investigate the need for the use and application of digital tools in the MSMEs of Xicotepec, analyze the expectations of training and evaluate the impact of the pandemic on the perception of the need for training"Materials and methods: Information was collected through interviews with 20 microentrepreneurs, capturing data on the perception, importance and impact of training in: use and application of technological tools to improve their administrative management.Results. It is indicated that there is knowledge of the new tools, there is a LACK of use of them in their entirety in MSMEs.Discussion: The qualitative research revealed knowledge on the part of MSME entrepreneurs of the existence of innovative administrative management tools, but without exploiting their full potential for their benefit, giving the opportunity to carry out training agreements to contribute to regional economic development.Conclusions Technological innovations are fundamental for the development of MSMEs, the development of technical skills of use is lacking.Contribution/originality: Refers to the work: "Training in the management of digital tools and administrative management that promote the MSMEs of Xicotepec."
Keywords: Perspective; impact; digital tools; training; administrative management; digital marketing